Handbook of Information and Communication Security - Stavroulakis, Peter; Stamp, Mark.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The Handbook of Information and Communication Security covers some of the latest advances in fundamentals, cryptography, intrusion detection, access control, networking (including extensive sections on optics and wireless systems), software, forensics, and legal issues. The editors$1 (Bintention, with respect to the presentation and sequencing of the chapters, was to create a reasonably natural flow between the various sub-topics. This handbook will be useful to researchers and graduate students in academia, as well as being an invaluable resource for university instructors who are searching for new material to cover in their security courses. In addition, the topics in this volume are highly relevant to the real world practice of information security, which should make this book a valuable resource for working IT professionals. This handbook will be a valuable resource for a diverse audience for many years to come.s
Fundamentals and Cryptography -- A Framework for System Security -- Public-Key Cryptography -- Elliptic Curve Cryptography -- Cryptographic Hash Functions -- Block Cipher Cryptanalysis -- Chaos-Based Information Security -- Bio-Cryptography -- Quantum Cryptography -- Intrusion Detection and Access Control -- Intrusion Detection and Prevention Systems -- Intrusion Detection Systems -- Intranet Security via Firewalls -- Distributed Port Scan Detection -- Host-Based Anomaly Intrusion Detection -- Security in Relational Databases -- Anti-bot Strategies Based on Human Interactive Proofs -- Access and Usage Control in Grid Systems -- ECG-Based Authentication -- Networking -- Peer-to-Peer Botnets -- Security of Service Networks -- Network Traffic Analysis and SCADA Security -- Mobile Ad Hoc Network Routing -- Security for Ad Hoc Networks -- Phishing Attacks and Countermeasures -- Optical Networking -- Chaos-Based Secure Optical Communications Using Semiconductor Lasers -- Chaos Applications in Optical Communications -- Wireless Networking -- Security in Wireless Sensor Networks -- Secure Routing in Wireless Sensor Networks -- Security via Surveillance and Monitoring -- Security and Quality of Service in Wireless Networks -- Software -- Low-Level Software Security by Example -- Software Reverse Engineering -- Trusted Computing -- Security via Trusted Communications -- Viruses and Malware -- Designing a Secure Programming Language -- Forensics and Legal Issues -- Fundamentals of Digital Forensic Evidence -- Multimedia Forensics for Detecting Forgeries -- Technological and Legal Aspects of CIS.
Keywords: Engineering; Data protection; Data structures (Computer science).; Telecommunication; Engineering; Communications Engineering, Networks; Data Structures, Cryptology and Information Theory; Systems and Data Security